ISOLASI BAKTERI ENDOFIT BAWANG DAYAK (Eleutherine bulbosa) DAN UJI ANTAGONISME TERHADAP BAKTERI Escherichia coli DAN Staphylococcus aureus - Ebrry Dwi Putra; Frans Naibaho; Liswara Neneng; Desimaria Panjaitan (Bioma, 2023)
Antibiotic resistance is one of the main challenges faced by the health world today. Therefore, various efforts are being made to find new alternative antibiotics from various sources. Endophytic bacteria from medicinal plants are thought to have an antibacterial activity that can potentially inhibit pathogenic bacteria growth. This study aimed to isolate and characterize endophytic bacteria from the Dayak onion plant and determine their potential to inhibit the growth of two pathogenic bacteria Escherichia coli and Staphylococcus aureus. Bacterial isolation was carried out using the surface sterilization method and grown on nutrient agar media. The endophytic bacteria isolates obtained were then characterized macroscopically and microscopically. The agar plug diffusion method carried out the antagonism test against pathogenic bacteria. The result showed that 40 isolates of endophytic bacteria were successfully isolated from the Dayak onion plant's leaves, bulbs, and roots. Based on the antagonism test, 3 isolates were able to inhibit E.coli while 8 isolates were able to inhibit S. aureus. Three isolates (CED3, CED4, and CEU6) were able to inhibit both pathogenic bacteria, and the highest activity was shown by CED3 isolates.